Fieldwork in Lango, northern Uganda Feb-Mar 1997 - Cooke, Peter (International Library of African Music, 1999)
Very little academic research has been carried out into the rich and varied musical traditions of the north of the country in contrast with those of the relatively well-explored areas of Bantu-speaking southern Uganda. Yet acquaintances among the Baganda for instance, have often expressed their admiration of the attractive harp and zither music of the Acholi in the north. Less well-known are the lamellaphone-playing traditions of the same general area - notably those of the Acholi, their southern neighbours the Lango people and the Teso people (to the east of Lango). In 1968 a brief fieldwork visit to eastern Acholi had made me aware of widespread and spirited use of the lukeme (the Acholi term for their box-resonated lamellaphone) in ensembles of a dozen or more young men or boys - playing on instruments in three different sizes. Unfortunately the continuing activities of rebel groups belonging to the so-called 'Lord's Resistance Army' under their leader John Kony made it quite impracticable for me to visit any part of Acholi when in February 1997 I tried recently to follow up the initial research I made some 19 years earlier.
Keywords: Fieldwork; African Music; Uganda